Analisis Digitalisasi Sistem Perpajakan dan Efisiensi Pelayanan Pajak di Indonesia - Alfida Nesa Mara; Ida Farida Adi Prawira; Rika Nurrizkiana (Universitas Katolik Soegijapranata, Semarang, 2026)
This literature study examines how the digitization of the taxation system has impacted the efficiency of tax services in Indonesia. The Directorate General of Taxes (DGT) has taken advantage of rapid advances in information technology to implement digital systems such as e-Filing, e-Billing, and e-Invoicing to speed up service processes, reduce administrative errors, and improve taxpayer compliance. However, there is still debate about how effective this digitization is in improving efficiency. While some studies show savings in time and costs, other studies point to problems such as poor digital literacy, system disruptions, and infrastructure limitations, especially in certain regions and among MSMEs. This study aims to examine and synthesize previous research findings on the relationship between digital tax systems and service efficiency, as well as to identify factors that support and hinder their implementation. This study investigates literature published between 2015 and 2025 using qualitative descriptive analysis (literature review). The results consistently show that digitization, including regional applications and the CoreTax System initiative, can improve administrative efficiency by reducing processing time, compliance costs, and input errors. To achieve efficiency, a good technical system, continuous socialization, digital readiness and literacy of human resources (officials and taxpayers), and synergistic regulatory support are essential. According to this study, the reliability of technical platforms and continuous investment in human resource training and digital literacy should be prioritized, especially for small and medium-sized enterprises (SMEs).